The evaluation of different levels diets protein for growth performance of Clarias sp. fry cultured in biofloc-based system - Noviati Rohmatul Khasanah; Nur Bambang Priyo Utomo; Mia Setiawati; Munti Yuhana (Jurnal Akuakultur Indonesia)
ABSTRACT